Fast Determination of Imidacloprid in Beeswax by Liquid Chromatography Coupled to Electrospray-Mass Spectrometry - P. Yanez, Karen; L. Bernal, Jose; J. Nozal, Maria; T. Martin, Maria; Bernal, Jose (Current Analytical Chemistry, 2013)
Bee losses associated with colony collapse disorder (CCD) has become a serious worldwide problem. Over 60 contributing factors of CCD have been identified, being one of them the pesticide exposure, and particularly to neonicotinoid pesticides as imidacloprid. So, it is interesting to study its possible presence in beeswax, as this product could be a storage location of this pesticide not only for its original beehive, but for other beehives where some of the beeswax could be used as foundation. A simple and fast method has been developed to measure imidacloprid in beeswax based on liquid chromatography (LC) coupled to an electrospray ionization mass spectrometry (ESI-MS) detection. Beeswax was diluted in a nhexane/ isopropanol mixture, and it was performed a liquid-liquid extraction with water. The aqueous phase was passed through a diatomaceous material based cartridge, and the analytes were eluted with acetone. This eluate was evaporated to dryness and reconstituted with a mixture of 0.1% formic acid and acetonitrile. A Kinetex C18 analytical column (150 × 4.6 mm i.d.) was used and the mobile phase selected was a 50:50 (v/v) mixture of water at pH 7 and methanol in isocratic elution mode. This method was fully validated in terms of selectivity, linearity, precision and trueness and the limits of detection (LOD) and quantification (LOQ) were 0.1μg/kg and 0.5 μg/kg respectively. Finally, the proposed method has been applied to the analysis of beeswax samples from Spanish apiaries located close to fruit trees.
Keywords: SPE